Effect of rotating twisted tape on thermo-hydraulic performances of nanofluids in heat-exchanger systems. (15th June 2018) - Qi, Cong; Wang, Guiqing; Yan, Yuying; Mei, Siyuan; Luo, Tao
Graphical abstract: Highlights: Exergy-resistance instead of thermo-hydraulic of nanofluids is analyzed. Effects of rotating instead of static twisted tape on nanofluids are studied. Rotating twisted tape with nanofluids can enhance heat transfer by 101.6%. Abstract: Stable TiO2 -H2 O nanofluids are prepared and their stabilities are studied. An experimental set for studying the heat transfer and flow characteristics of nanofluids is established. Heat transfer and flow characteristics of TiO2 -H2 O nanofluids in a circular tube with rotating and static built-in twisted tapes are experimentally investigated and compared. An innovative performance evaluation plot of exergy efficiency is developed and the exergy efficiency of tube with rotating and static built-in twisted tapes filled with nanofluids is analyzed in this paper. The results indicate that the combination of rotating built-in twisted tape and TiO2 -H2 O nanofluids shows an excellent enhancement in heat transfer, which can increase the heat transfer by 101.6% compared with that of in a circular tube. The effects of nanoparticle mass fractions ( ω = 0.1%, 0.3% and 0.5%) and Reynolds numbers ( Re  = 600–7000) on the heat transfer and flow characteristics of TiO2 -H2 O nanofluids are discussed. It is found that there is a critical Reynolds number ( Re  = 4500) for the maximum value of relative heat transfer enhancement ratio. The comprehensive performance of the experimental system is analyzed. It can be found that the comprehensive performance index of the experimental system firstly increases and then reduces with Reynolds number, and it can reach 1.519 at best. However, for the performance evaluation of exergy efficiency, the coupling of rotating twisted tape and nanofluids deteriorates the exergy efficiency. Also, it can be found that the exergy efficiency of the circular tube with twisted tape is greater than that of circular tube under the same pumping power and pressure drop, but it shows deterioration under the same mass flow rate.